The Effectiveness Of Atomic Structure And Chemical Element (Islamic Perspective) Book - Siska Oktapianti (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
A book based on the integration of science and Islam can make it easier for students to understand the material and improve learning outcomes. The aim of this study is to determine the effectiveness of the book : Atomic Structure and Chemical Element (Islamic Perspective). The type of the research is field research with the design: pretest - posttest control group design. The sample is 10 Tadris Chemistry Students for the Atomic Structure and Chemical Element Class, Odd Semester 2022/2023 selected to ensure a representative group. Data collection techniques are interview, documentation, and test question. The data are analyzed by using the N-Gain test. The average N-Gain score of students is 0.6 in the moderate category. The results of the N-Gain of students show that the book developed can improve students' knowledge and understanding. This explains that the learning outcomes of the cognitive aspect have increased. The results of the study on a small scale prove that the book developed is suitable in chemistry learning on the material Atomic Structure and Chemical Element and can be effective in improving student understanding.